Direct and spillover effects of agricultural advisory services: Evidence from the farm science centre in Uttar Pradesh, India - Varshney, Deepak; Joshi, Pramod Kumar; Dubey, Shantanu Kumar (International Food Policy Research Institute, 2019)
Agricultural advisory services are the most important knowledge-delivery institutions for accelerating the adoption of advanced technologies, and for improving farmers’ learning abilities for their implementation. These technologies have implications for the larger goal of agricultural development and farmers’ welfare. This study explores the spillover effects of an innovative public-sector program in India that provides agricultural advisory services. At the Farm Science Centre (known locally as Krishi Vigyan Kendra [KVK]), scientists demonstrate modern technologies and develop capacity-building programs. This paper examines the extent of direct and spillover benefits of KVKs. It also evaluates the impact of KVKs on the adoption of improved technologies for primary beneficiaries (those who receive the benefits directly from KVKs), and for those farmers who receive information flow from them. The study is based on a primary survey of 1,496 wheat farmers in Uttar Pradesh, India. Spillover information flows are captured by: a) farmers who visit frontline demonstration (FLD) sites by their own curiosity and are categorized as secondary beneficiary farmers, and b) farmers who obtain information flows from primary and secondary beneficiaries being in their social network and are categorized as network beneficiary. Identification is achieved by exploiting non-universal coverage of KVKs, and through the availability of recall-based panels for pre- and post-intervention years on the adoption of improved technologies. The study applied matched difference-in-difference (MDID) approach to examine the effect of frontline demonstrations (FLDs) and training programs. It also examine pre-intervention trends to provide a check on the validity of our estimates. Findings revealed that 3% of primary beneficiaries of FLDs can generate information spillover to 31% of farmers. For capacity building, the results showed that 3% of primary beneficiaries can generate information spillover to 27% of farmers. The key channel for spillover information flow was the network beneficiary. On a further note, the study establishes evidence of a positive impact on the adoption of a modern wheat variety—namely HD-2967—by primary beneficiaries, as well as secondary and network beneficiaries. Consistent with the information transmission channels, the magnitude of impact estimates are highest for primary followed by secondary and network beneficiaries. From a policy perspective, the study suggests a scaling-up of KVK’s interventions. Establishing evidence on the role of social network channel to diffuse information flows for public-sector programs provides new insights for strengthening the outreach of such programs. Moreover, the evidence of intra-regional spillover effects have an implications for accounting these effects in conducting a cost-benefit analysis of these programs.